Sensitivity of project 8344 model to price and quality parameters. - A. Ghaffar, Roslan; Yahya, Salleh; Chew, T. A. (1987)
Project 8344 model is a spatial equilibrium model that incorporates all the important diverse elements in the paddy post-harvest industry in Tanjung Karang. As the background for this paper, the model is first briefly described, calibrated and used to assess the economic viability of the introduction of the semi-bulk grain handling system in the area. It was found that the semi-bulk system is an acceptable economic proposition. Changes were then inflicted on the model to evaluate the robustness of our results to variations in selected key parameters. The results show that the sensitive variables, in descending order, are the price paid for paddy, the rice recovery rate, drying cost and milling cost. The sensitivity of the rice recovery rate has important policy implications. The effect of the closure of one mill and 19 procurements centres that are currently underutilised in our model was also tested. We obtained an increase in net industry loss of 14.6%, which is small, compared to 11.6% change accruing from a 1% change in rice recovery rate. Hence considerable welfare gains may be obtained by reducing and reorganising the existing procurement and processing points in Tanjung Karang.